Variation in flavonoid and antioxidant activities of Pyrrosia petiolosa (Christ) Ching from different geographic origins - Chen, Jianhua; Ning, Shan; Lu, Xuan; Xiang, Wei; Zhou, Xiao; Bu, Yuanyuan; Li, Liangbo; Huang, Rongshao (Frontiers in Plant Science, 2023)
Pyrrosia petiolosa (Christ) Ching has both medicinal and health benefits in China. The potential antioxidant activities of P. petiolosa, which are mainly attributed to its flavonoids, have attracted much attention in recent years. The present study aimed to determine the concentration of flavonoid components and evaluate the relative antioxidant activities of P. petiolosa from different geographic origins using a UPLC-MRM-MS-based metabolomics approach. In total, 97 flavonoid components were identified, and their concentrations in the samples from different geographic locations showed significant variation. Thirteen flavonoid components were identified as potential biomarkers for distinguishing between the two major regions, Guizhou (GZ) and Guangxi (GX). The GZ group showed higher total flavonoid content, free radical scavenging activities, and ferric reducing antioxidant power. The well positive correlations were found between the antioxidant capacities and some flavonoid markers. The ecogeographic factors, namely altitude and longitude, play a crucial role in the difference of antioxidant activities and flavonoids concentration. These results indicate that P. petiolosa is rich in flavonoid compounds and is a promising source of natural antioxidants, providing a basis for the quality control of P. petiolosa.